IMPLEMENTATION MODEL OF QARD AL HASAN FOR INDONESIAN ISLAMIC BANKING - Rachmawaty, Rachmawaty; Zaerofi, Afif; Jati, Waluyo (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2021)
It is challenging for Islamic banking as a business institution to provide qard al hassan. In this paper, we proposed qard al hassan platform (QHP) as the model which can be implemented for Islamic banking. QHP can use an internet base where the synergy of public to give fund through social crowdfunding and the capability of bank to provide good corporate governance in managing fund and assessment qard al hassan as financing in productive sector. Since there is no fee of qard al hassan to finance operational cost, there are 3 sources will be proposed. First is money from fee for Amil Zakat, second is profit of some portions of collection fund investment, and third is a profit of investment of the upfront payment of qard al hassan. Methodology to calculate upfront payment refer to Mesbah Point. Regarding minimizing and controlling the default rate, the bank should focus on the right target market of borrower and low risk industry sectors. Implementing QHP model can reduce poverty and achieve sustainable growth in society while at the same time creating the fairness of wealth distributing. The needy and the poor can participate in production and create its own wealth. However, the implementation of QHP could not be implemented without adjustment in regulation and set up infrastructure. Regulators need to give bank permission to collect zakat, sadaqah, cash waqf from public and as wakil of funder to execute QHP and together with banking industry to set up the infrastructures.